Relationship between Formal Reasoning and Understanding of Physics Concepts for Eleventh Grade Students: A Case of SMAN 3 Wajo - Zalzabila, Besse Nadifa; Arafah, Kaharuddin; Hashim, Mutahharah (Jurnal Pendidikan MIPA, 2023)
This research is a correlational descriptive study that aims to describe formal reasoning and understanding of physics concepts and the relationship between the two. The population in this study were all students of class XI MIPA SMAN 3 Wajo, while the number of samples based on the Proportional Random Sampling technique was 135 students. The instrument research is in the form of formal reasoning test instruments and understanding of physics concepts. Instrument validation used the Gregori test and continued with empirical validation Data analysis techniques performed consisted of descriptive statistical analysis and inferential statistical analysis. Based on the descriptive statistical analysis, it was found that the students' formal reasoning and conceptual understanding were in the medium category. Meanwhile, based on inferential statistical analysis, the results of the product-moment correlation test obtained an r count of 0,584. The value of the r count which is positive indicates the relationship between variables is positive. The results of the significance test obtained 0,01<0,05 so it can be said that the relationship between formal reasoning and understanding of physics concepts is significant. So it can be concluded that the relationship between formal reasoning and conceptual understanding is positive and significant. Keywords: physics learning, formal reasoning, conceptual understanding.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp72-83